FINANCIAL EDUCATION AND LITERACY BY MAINTAINING RUPIAH QUALITY FOR ISLAMIC PRIMARY SCHOOL STUDENTS - Ramadhani, Astri Ramadhani; Dhiba, Farah Dhiba; Salsabila, Salsabila; Salsabila, Sarah Salsabila; Azhari, Syah Putri Azhari; Siregar, Siregar; AK, Marlya Fatira AK; Nizma, Cut Nizma; Siregar, Rumnasari Khoiriyah Siregar (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
PKM Education on the Importance of Maintaining the Quality of Rupiah at Tunas Mekar Islamic Private Elementary School, Binjai Village, Medan Denai District, Medan City, North Sumatra. It aims to provide an Understanding of How to Care for Rupiah, the Difference Between Genuine and Fake Rupiah, and How to Save from an Early Age. The school has received Education related to the material from any party. For the PKM activities to run smoothly, the service team conducted data collection techniques through interviews—at the Islamic Private Elementary School Tunas Mekar. The solution is to find knowledge transfer through an Educational Seminar on the Importance of Maintaining the Quality of the Rupiah. The cost of implementing the PKM activity is Rp. 592,000.00 (Five Hundred and Ninety-Two Thousand Rupiah) and requires physical facilities of genuine and counterfeit Rupiah and souvenirs and certificates from Bank Indonesia. After carrying out community service activities in the form of training and seminars for students, the results of the service were obtained that The low literacy of maintaining the quality of the Rupiah at SDS Islam Tunas Mekar has been overcome through educational activities such as providing education about the history of the Rupiah, the nominal value of the Rupiah, love and pride in understanding the Rupiah, the difference between genuine and counterfeit Rupiah, literacy in saving from an early age and digital money, such as training to recognize genuine and counterfeit Rupiah using a money detector. This activity successfully formed students' knowledge and skills about maintaining the quality of the Rupiah to reach an average of 72% with a maximum understanding of 98% for all participants. The absence of an educational program that specifically discusses the importance of maintaining the quality of the Rupiah, which also supports social science lessons in the context of economic life activities, is a challenge that needs to be overcome. Two young ambassadors who deeply love the Rupiah and understand its essential value have been presented to address this issue. These young ambassadors are expected to not only provide an understanding to their peers about the importance of maintaining the currency's value but also encourage them to be more actively involved in activities that support the stability and quality of the Rupiah. With an exciting and creative approach, it is hoped that they can disseminate this knowledge more widely, creating awareness among students about the shared responsibility in maintaining the national economy.